From the first equation
6x - y = 1
6x - y - 1 = 0
6x - 1 = y
Substituting we get
4x - 3(6x - 1) = -11
Answer:
- 8x + 9
Step-by-step explanation:
To evaluate g(2x - 1) substitute x = 2x - 1 into g(x), that is
g(2x - 1)
= - 4(2x - 1) + 5 ← distribute parenthesis and simplify
= - 8x + 4 + 5
= - 8x + 9
The answer is 29, I just didn’t on my head right now.
You have to subtract 5x since its positive bring it to the other side then divide with negative one with everything which you get you y = 5- 5x
the slope is five over one
the y intercept is 5